Relevansi Kebijakan Desentralisasi dengan Konsepsi Negara Kesatuan - Andi Kasmawati (Faculty of Law, Universitas Diponegoro, 2012)
Abstract The agreement at the beginning of the reform of the Indonesian nation to maintain the Unitary State, following a suggestion to change into a federal state, a cornerstone of government formation to accommodate both forms of the country by replacing Law. 1974 on regional administration, which tend to be centralized, with Law no. 22, 1999 are decentralized, the way this law causes a lot of tension and problems relating to local government authorities, thus replaced by Law no. 32 of 2004 which diharpkan able to resolve the issue. The concept of a unitary state in the government putting As with sub-national governments are delivered / transferred desentraliasasi government based on the theory that one theory of the delegation of authority in local government, it is not relevant to the theory of decentralization G. Cheema and Rondinelly, but the conception of the unitary state of Indonesia are relevant to the theory of imperfect decentralization proposed by Hans Kelsen. Key Words: Decentralization and Unity state Abstrak Kesepakatan bangsa Indonesia di awal reformasi untuk tetap mempertahankan Negara Kesatuan, setelah ada wacana untuk merubah menjadi negara federal, menjadi landasan pembentukan pemerintahan yang mengakomodir kedua bentuk negara tersebut dengan mengganti UU No. Tahun 1974 tentang Pemerintahan daerah, yang cenderung sentralistik, dengan UU No. 22 Tahun 1999 yang desentralistik, dalam perjalanannya UU ini banyak menimbulkan ketegangan dan permasalahan yang berkaitan dengan kewenangan pemerintahan daerah, sehingga diganti dengan UU No. 32 Tahun 2004 yang diharpkan mampu mengatasi masalah tersebut. Konsep negara kesatuan dalam pemerintahan menempatkan pemerintah daerah sebagi sub nasional yang diserahkan/dilimpahkan pemerintah berdasarkan teori desentraliasasi yang salah satu teori pelimpahan wewenang dalam pemerintah daerah, tidak relevan dengan teori desentralisasi G. Cheema dan Rondinelly, namun konsepsi negara kesatuan di Indonesia relevan dengan teori desentralisasi tidak sempurna yang dikemukakan oleh Hans Kelsen. Kata Kunci: Desentarlisasi dan Negara Kesatuan